Exogenous melatonin treatment reduces postharvest senescence and maintains the quality of papaya fruit during cold storage - Wang, Dengliang; Randhawa, Mazhar Saeed; Azam, Muhammad; Liu, Hongru; Ejaz, Shaghef; Ilahy, Riadh; Qadri, Rashad; Khan, Muhammad Imran; Umer, Muhammad Ali; Khan, Muhammad Arslan; Wang, Ke (Frontiers in Plant Science, 2022)
Exogenous melatonin (MLT) application has been used to reduce the postharvest senescence and improve quality and antioxidant enzyme activities of papaya fruit during cold storage. Therefore, in the present study impact of exogenously applied melatonin (1.5 mM L-1) was investigated on papaya fruits during cold storage (10 ± 2 ºC) for 28 days. The results showed that MLT treatment was notably suppressed postharvest senescence and weight loss than untreated control papaya fruit. MLT-treated papaya fruit significantly suppressed the increase of soluble solid contents, ripening index and sugars, and substantially higher titratable acidity and ascorbic acid compared with control. In addition, papaya fruit treated with MLT showed markedly higher total phenolic contents resulting in higher total antioxidant activity in contrast with control papaya fruits. Besides, MLT treatment significantly inhibited the accumulation of hydrogen peroxide and malondialdehyde, while maintaining higher level of superoxide dismutase and peroxidase and catalase antioxidant enzymes along with higher sensory attributes than untreated control. The findings of this study indicated that MLT application could be commercially used as safer and valuable strategy to reduce the postharvest senescence and maintain the quality traits of papaya fruit during cold storage.